Sensory innervation in the prostate and a role for calcitonin gene-related peptide in prostatic epithelial proliferation - Xia, Hanyu; Jerde, Travis J.; Fehrenbacher, Jill C. (Frontiers in Molecular Neuroscience, 2024)
IntroductionThe prostate is densely innervated like many visceral organs and glands. However, studies to date have focused on sympathetic and parasympathetic nerves and little attention has been given to the presence or function of sensory nerves in the prostate. Recent studies have highlighted a role for sensory nerves beyond perception of noxious stimuli, as anterograde release of neuropeptides from sensory nerves can affect vascular tone and local immune responses.MethodsTo identify the degree of sensory innervation in the prostate, we utilized state-of-the-art tissue clearing and microscopy to visualize sensory innervation in the different lobes of the mouse prostate. To determine whether sensory nerves have a role in regulating proliferation within the prostate, we used an intersectional genetic and toxin approach to ablate peptidergic sensory nerves systemically.ResultsWe found that sensory neurons are abundant in the prostate both in nerve bundles along the vasculature and as independent nerve fibers wrapped around prostatic acini in a net-like fashion. In addition to the dense innervation of the prostate, we found that Calca haploinsufficiency, the genotype control for our intersectional ablation model, results in a diminished level of Ki67 staining in the stromal compartment of the dorsal lobe and a diminishing Ki67 trend in other lobes.DiscussionThese findings suggest that sensory neurons might have developmental or homeostatic effects within the prostate. Further studies are warranted to assess the role of sensory neurons and the sensory neuropeptides on prostatic development and on proliferation in the presence of pro-inflammatory stimuli such as bacterial infection or tumor cells.